Phenotyping: Targeting genotype’s rich cousin for diagnosis - Baynam, G.; Walters, M.; Claes, P.; Kung, S.; LeSouef, P.; Dawkins, Hugh; Bellgard, M.; Girdea, M.; Brudno, M.; Robinson, P.; Zankl, A.; Groza, T.; et al. (Blackwell Scientific Publications, 2015)
There are many current and evolving tools to assist clinicians in their daily work of phenotyping. In medicine, the term ‘phenotype’ is usually taken to mean some deviation from normal morphology, physiology and behaviour. It is ascertained via history, examination and investigations, and a primary aim is diagnosis. Therefore, doctors are, by necessity, expert ‘phenotypers’. There is an inherent and partially realised power in phenotypic information that when harnessed can improve patient care. Furthermore, phenotyping developments are increasingly important in an era of rapid advances in genomic technology. Fortunately, there is an expanding network of phenotyping tools that are poised for clinical translation. These tools will preferentially be implemented to mirror clinical workflows and to integrate with advances in genomic and information-sharing technologies. This will synergise with and augment the clinical acumen of medical practitioners. We outline key enablers of the ascertainment, integration and interrogation of clinical phenotype by using genetic diseases, particularly rare ones, as a theme. Successes from the test bed or rare diseases will support approaches to common disease.